2013
DOI: 10.1007/s10661-013-3387-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of northeast monsoon on trace metal distribution in the South China Sea off Peninsular Malaysia

Abstract: Concentrations of trace metals in the South China Sea (SCS) were determined off the coast of Terengganu during the months of May and November 2007. The concentrations of dissolved and particulate metals were in the range of 0.019-0.194 μg/L and 50-365 μg/g, respectively, for cadmium (Cd), 0.05-0.45 μg/L and 38-3,570 μg/g for chromium (Cr), 0.05-3.54 μg/L and 21-1,947 μg/g for manganese (Mn), and 0.03-0.49 μg/L and 2-56,982 μg/g for lead (Pb). The order of mean log K D found was Cd > Cr > Pb > Mn. The study sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…Similar findings were recorded by Fortune and Mauraud 38 , where they found the highest DO values at high tide and lowest values at low tide. These findings were comparable to Adiana et al, 39 ; Suratman et al, 40 and the Malaysian Meteorological Data reports by Sang et al, 37 . The variations in DO indicated a temporal pattern since DO change with tides condition 38 for PP1 and PP2.…”
Section: Physicochemical Characteristics Of the Water Columnsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar findings were recorded by Fortune and Mauraud 38 , where they found the highest DO values at high tide and lowest values at low tide. These findings were comparable to Adiana et al, 39 ; Suratman et al, 40 and the Malaysian Meteorological Data reports by Sang et al, 37 . The variations in DO indicated a temporal pattern since DO change with tides condition 38 for PP1 and PP2.…”
Section: Physicochemical Characteristics Of the Water Columnsupporting
confidence: 90%
“…However, this study was done in a simulation laboratory, where the pH range was controlled. Previously, dissolved trace metals in seawater samples were done in Peninsular Malaysia by Adiana et al, 15 and Godon and Mohamed 16 , where their findings suggested comparable range of dissolved trace metals concentrations with effects from the Northeast monsoon in Terengganu coastal area. Unfortunately, no speciation data reported for both studies.The main concern about monsoon is that it could alter the physical-chemical parameters and affect the trace metal speciation.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Recently, Shi et al (2015) [7] and [8] discussed clay mineral and elemental distributions, respectively, in the western Gulf of Thailand, which neighbours the study area to the northwest. Until now, limited work on sediment compositions, except for trace metal and rare earth elemental compositions, has been conducted in the WSSMP [9][10][11]. Multi-proxy studies from the land to the ocean are required to better understand the compositions and spatial distributions of sediments on the Sunda Shelf in the southern SCS.…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium (Cd) is a serious environmental pollutant which occurs naturally, it could be released into environments by natural processes and human activities [1]. There exists certain amounts of Cd in different rivers and sea waters [2, 3]. In some developing countries, such as China, the Cd level is much higher in the severely polluted aquatic environments.…”
Section: Introductionmentioning
confidence: 99%